First and Fourteenth Amendment Issues with Florida’s ‘Don’t Say Gay’ Bill - Rebecca Flynn (Washington University Journal of Law and Policy, 2024)
Florida’s 2022 passage of the “Parental Rights in Education” bill, better known as the “Don’t Say Gay” bill, prohibited classroom instruction related to sexual orientation or gender. The broad, vague language of the “Don’t Say Gay” law and questionable motivations of the legislation have created Constitutional tension between parental rights and minor’s’ rights in the educational settings. By highlighting the history of anti-gay curriculum laws, this Note argues that Florida’s “Don’t Say Gay” law and similar anti-gay curriculum laws reflect the prioritization of parental rights over minors’ right and highlight First Amendment free speech and Fourteenth Amendment Equal Protection concerns. Students are harmed by “Don’t Say Gay” laws that reflect parental concerns because these laws silence diverse student populations, place private and traditional values above educational opportunities, and create hostile educational environments.
Keywords: DontSayGay; ParentalRights; LGBTQEducation; FirstAmendment; EqualProtection